Revived and Discouraged: Evaluating Employment Barriers for Section 3 Residents With Criminal Records. Issue 2 (3rd March 2016) - Walter, Rebecca J.; Caudy, Michael; Ray, James V.
Abstract: Section 3 was established in the Housing and Urban Development (HUD) Act of 1968 to provide employment for public housing residents in distressed communities while rebuilding underserved neighborhoods. As a provision that recipients of HUD funding must comply with, Section 3 reporting agencies are having trouble securing employment for ex-offenders. This is problematic since low-income ex-offenders unable to secure stable employment are more likely to recidivate. Research evaluating the specific barriers to employment for Section 3 residents with criminal records and policy recommendations are sparse although the problem is prevalent in communities nationwide. This study uses San Antonio, Texas as an example for conducting a policy review to identify the barriers to employment for Section 3 ex-offenders. The results of the qualitative analysis indicate that at the national level, HUD and the Section 3 provision do not create barriers to employment but state and local policies and practices do.